On the Origin of the Large Remanent Polarization in La:HfO2 - Schenk, Tony; Fancher, Chris M.; Park, Min Hyuk; Richter, Claudia; Künneth, Christopher; Kersch, Alfred; Jones, Jacob L.; Mikolajick, Thomas; Schroeder, Uwe (Advanced electronic materials, 2019)
The outstanding remanent polarization of 40 µC cm–2 reported for a 10 nm thin La:HfO2 film in 2013 has attracted much attention. However, up to now, no explanation for this large remanent polarization has been presented. Density functional theory and X‐ray diffraction are used to shine light onto three major aspects that impact the macroscopically observed remanent polarization: phase fraction, spontaneous polarization, and crystallographic texture. Density functional theory calculations show that the spontaneous polarization (Ps) of La:HfO2 is indeed a bit larger than for other HfO2‐ or ZrO2‐based compounds; however, the Ps is not large enough to explain the observed differences in remanent polarization. While neither phase fractions nor spontaneous polarization nor strain are significantly different from those in other HfO2 films, a prominent 020/002 texture distinguishes La doped from other HfO2‐based ferroelectric films. Angular‐dependent diffraction data provide a pathway to calculate the theoretically expected remanent polarization, which is in agreement with the experimental observations. Finally, an interplay of the in‐plane strain and texture is proposed to impact the formation of the ferroelectric phase during annealing. Further aspects of the special role of La as a dopant are collected and discussed to motivate future research. The origin of the large remanent polarization in La:HfO2 thin films is investigated. Density functional theory calculations suggest a larger spontaneous polarization for the incorporation of La compared to other dopants. In‐depth X‐ray diffraction analysis together with Rietveld refinement allows for the derivation of the stress state of the film and the role of crystallographic texture.